Measuring Well-Being 2021
DOI: 10.1093/oso/9780197512531.003.0016
|View full text |Cite
|
Sign up to set email alerts
|

Inner Peace as a Contribution to Human Flourishing

Abstract: Although philosophers and theologians have emphasized the centrality of inner peace for the good life, this concept has not generally been included in research on human flourishing. The authors argue that inner peace contributes to a more complete form of flourishing for both religious and secular people. They then propose a new instrument, the Inner Peace Scale, to measure inner peace, and they provide an initial psychometric evaluation of the instrument based on five empirical studies. The authors distinguis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…Empirical research has been able to confirm some of the pathways that we would expect in light of the wisdom of the humanities. To take just one example, it appears that it is indeed "better to give than to receive", as a preoccupation with hedonistic enjoyment may adversely affect a sense of inner peace or personal growth, while participation in benevolent service to others is associated with a variety of positive well-being outcomes [8,35]. In the same vein, we found that the increased importance of character strengths showed little evidence of association with the domains of physical health and emotional health, and was negatively associated with the financial stability domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research has been able to confirm some of the pathways that we would expect in light of the wisdom of the humanities. To take just one example, it appears that it is indeed "better to give than to receive", as a preoccupation with hedonistic enjoyment may adversely affect a sense of inner peace or personal growth, while participation in benevolent service to others is associated with a variety of positive well-being outcomes [8,35]. In the same vein, we found that the increased importance of character strengths showed little evidence of association with the domains of physical health and emotional health, and was negatively associated with the financial stability domain.…”
Section: Discussionmentioning
confidence: 99%
“…These domains comprise emotional health, purpose in life, social connectedness, character strengths, physical health, and financial security [3,5], and have been shown to be highly valued by people [3,6]. Most people throughout the world would also insist on including additional well-being domains, such as spirituality [7] or inner peace [8]. Consideration of community well-being, which involves more than a simple aggregation of individuals' self-reported well-being, is also desirable [9].…”
Section: Introductionmentioning
confidence: 99%
“…Meaning in life consists of an 'attachment to something larger, and the larger the entity to which you attach yourself, the more meaning in your life' (Seligman, 2002, p. 14). Attachment to the inner self and the outer world could enhance human flourishing (Xi and Lee, 2021). Therefore, planetary citizenship is linked to human growth towards being a person who is aware, reflective and free of prejudice, and who can look at the world from new perspectives; for example, by imagining the world from the perspective of a plant, a rock or an unborn child (Baril, 2021).…”
Section: Planetary Citizenship Is About Spatial Temporal and Ethical ...mentioning
confidence: 99%
“…For experiences of planetary inclusion, we propose the position: 'I live in peace and harmony with the world'. This is a basic factor of eudaimonic well-being (Xi and Lee, 2021).…”
Section: Claim 9 -'I Feel Trusted'mentioning
confidence: 99%
“…Incorporating mindfulness into daily rituals, such as mindful eating, breathing exercises, and gratitude journaling, can bring attention to the present moment and enhance overall well-being [ 33 ]. Mindful practices encourage a greater sense of awareness and appreciation for the experiences that shape daily life, fostering an outlook of mindfulness that aligns with the principles of dopamine fasting and wellness [ 34 ]. Holistic wellness involves incorporating practices like nature connection and mindfulness into daily routines, fostering social connections through meaningful conversations, group activities, and volunteering, and nurturing community relationships to enhance well-being and create a supportive environment [ 35 ].…”
Section: Reviewmentioning
confidence: 99%